GE_GERICHTE P/20125/2022 vom 2. September 2024 - GE Cour de justice (2024)
DISPOSITIONS PÉNALES DE LA LSTUP;FIXATION DE LA PEINE;PEINE D'ENSEMBLE;RÉVOCATION DU SURSIS;EXPULSION(DROIT PÉNAL) | Lstup.19; Lstup.19a; CP.47; CP.49; LCR.90; LPG.11C; LPG.110; CP.66abis